Association of sedentary behavior with overweight and abdominal obesity in older adults - Talita Inácio Martins Resende; Joilson Meneguci; Jeffer Eidi Sasaki; Álvaro da Silva Santos; Renata Damião (Revista Brasileira de Atividade Física e Saúde)
The aim of this study was to examine the association of sedentary behavior with overweight and abdominal obesity in older adults. This was a cross-sectional study with older men and women residing in the municipalities of the Regional Health Superintendency of Uberaba, Minas Gerais. Sedentary behavior was assessed according to the time spent sitting on a weekday and a weekend day. Body mass, height and waist circumference were measured. Excess weight was determined by means of body mass index, while abdominal obesity by waist circumference. Poisson regression analyzes with robust variance were used to examine the association of sedentary behavior with overweight and abdominal obesity. The total sample consisted of 3223 older people (61.3% women), with a mean age of 70 ± 7.26 years. There was no association between quartiles of sedentary behavior and overweight (2nd quartile: PR = 0.99; 95%CI: 0.94–1.05; 3rd quartile: PR = 0.99; 95%CI: 0.93–1.07; 4th quartile: PR = 1.07; 95%CI: 1.00–1.13) and abdominal obesity (2nd quartile: PR = 1.04; 95%CI: 1.00–1.08; 3rd quartile: PR = 1.03; 95%CI: 0.98–1.08; 4th quartile: PR = 0.98; 95%CI: 0.94–1.03) when analyses were adjusted for sociodemographic, health perception and behavioral variables. The sedentary behavior was not associated with overweight and abdominal obesity in the elderly.